1996
DOI: 10.1021/ma951515r
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo Simulation of Asymmetric Random Copolymers at an Immiscible Interface

Abstract: The distribution of a random copolymer P(A f -r-B1-f ) at the interface between immiscible A and B phases as a function of the copolymer composition, denoted by the fraction f of A monomers, and as a function of the monomer−monomer interactions, or χ values, has been studied via lattice Monte Carlo simulations. A symmetric distribution of the copolymer was found for compositionally symmetric chains (f = 0.5) when the χ values were independent of the copolymer composition. In contrast, an asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…(1) [15] qualitatively, with g SM 0.8 ergs͞cm 2 and d͑Dg͒͞df 2g SM ϳ 1.6 ergs͞cm 2 . Dg was equal to zero at f 0.57 6 0.05 rather than at f 0.5 (indicating that x AB is concentration [23] and composition [24,25] dependent). The linear increase of c͑d͒ observed here, for f .…”
mentioning
confidence: 94%
“…(1) [15] qualitatively, with g SM 0.8 ergs͞cm 2 and d͑Dg͒͞df 2g SM ϳ 1.6 ergs͞cm 2 . Dg was equal to zero at f 0.57 6 0.05 rather than at f 0.5 (indicating that x AB is concentration [23] and composition [24,25] dependent). The linear increase of c͑d͒ observed here, for f .…”
mentioning
confidence: 94%
“…Previous investigations have indicated that random copolymers are surprisingly effective in reinforcing polymer–polymer interfaces 1–12. The strength of such interfaces is of critical importance in a number of applications, including semiconductor packaging, fiber optics, biomedical devices, pressure sensitive adhesives, and polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 An important goal of our work was to determine the predominant strengthening mechanism for copolymer layers coated at homopolymer joints. We deduce that the relative interactions of the copolymer with each homopolymer phase plays a role in determining the locus of fracture, and hence the apparent strength of the joint.…”
Section: Introductionmentioning
confidence: 99%
“…These results cannot adequately be explained by the "stitch" model, because random copolymers in "thick" layers cannot cross between the A and Our own study on P(S-ran-MMA) random copolymers at PS/PMMA joints parallels work being done by Brown and co-workers. 11,12 An important goal of our work was to determine the predominant strengthening mechanism for copolymer layers coated at homopolymer joints. We deduce that the relative interactions of the copolymer with each homopolymer phase plays a role in determining the locus of fracture, and hence the apparent strength of the joint.…”
Section: Introductionmentioning
confidence: 99%